Humans or animals? The linguistic representation of animal characters in original and translated Finnish picture books for children - Priiki, Katri; Kolehmainen, Leena (SAGE Publications, 2025)
This article examines pronominal references to anthropomorphic animal characters in contemporary Finnish-language picture books for children (N = 531). In the Finnish language, the choice of third person pronoun is a key means of distinguishing humans from other animals. The study shows that animal characters in children’s literature are linguistically placed between humans and nonhumans: in about half of the analysed books, the pronoun typically referring to humans refers to the animal characters, whereas in the other half of the data, the pronoun referring to nonhumans is used. A quantitative analysis reveals that the use of the human personal pronoun correlates with the number of human-like traits the characters possess. The analysis shows that pronoun variation has a variety of functions in picture books. Different pronouns may refer to different characters, indicating their degree of humanity, and the treatment of characters as human or nonhuman may also change as the story progresses. The human pronoun can be used in dialogue to indicate that the characters treat each other as persons. On the other hand, since there are differences in the Finnish pronoun system between the spoken and written variety, pronoun variation can mark a dialogue as colloquial. The study compares original and translated Finnish literature, revealing some differences. Finnish authors use the stylistic values linked to the pronouns as a resource more widely than translators, which results in more book-internal variation. Conversely, translators orient towards the standard language and consider how human-liken the characters are when choosing pronouns.